Managerial Opposition to Union Certification in Quebec and Ontario - Thomason, Terry; Pozzebon, Silvana (Relations industrielles / Industrial Relations, 1998)
Using data collected from a survey of union organizers, employer behavior during certification campaigns in Canada is examined. The extent and impact of opposition practices used by Quebec and Ontario employers during the late 1980s and early 1990s is investigated. It is found that prevalence of opposition tactics is not pronounced in either Quebec or Ontario. Nevertheless, these tactics are effective in reducing the level of union support in certification campaigns, if not the probability of certification. Most tactics examined appear to decrease the proportion of employees supporting the union, while captive audience speeches have a consistent negative and significant effect on certification probability.
Keywords: Attitudes; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Certification; Comparative analysis; Labor Unions; Managers; Membership drives; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Statistical analysis; Studies; Unionization